Building metamemorial knowledge over time: insights from eye tracking about the bases of feeling-of-knowing and confidence judgments - Chua, Elizabeth F.; Solinger, Lisa A. (Frontiers in Psychology, 2015)
Metamemory processes depend on different factors across the learning and memory time-scale. In the laboratory, subjects are often asked to make prospective feeling-of-knowing (FOK) judgments about target retrievability, or are asked to make retrospective confidence judgments (RCJs) about the retrieved target. We examined distinct and shared contributors to metamemory judgments, and how they were built over time. Eye movements were monitored during a face-scene associative memory task. At test, participants viewed a studied scene, then rated their feeling-of-knowing that they would remember the associated face. This was followed by a forced choice recognition test and retrospective confidence ratings. FOK judgments were less accurate than RCJ judgments, showing that the addition of mnemonic experience can increase metacognitive accuracy over time. However, there was also evidence that the given FOK rating influenced RCJs. Turning to eye movements, initial analyses showed that higher cue fluency was related to both higher FOKs and higher RCJs. However, further analyses revealed that the effects of the scene cue on RCJs were mediated by FOKs. Turning to the target, increased viewing time and faster viewing of the correct associate related to higher FOKs, consistent with the idea that target accessibility is a basis of FOKs. In contrast, the amount of viewing directed to the chosen face, regardless of whether it was correct, predicted higher RCJs, suggesting that choice experience is a significant contributor RCJs. We also examined covariates of the change in RCJ rating from the FOK rating, and showed that increased and faster viewing of the chosen face predicted raising one’s confidence above one’s FOK. Taken together these results suggest that metamemory judgments should not be thought of only as distinct subjective experiences, but complex processes that interact and evolve as new psychological bases for subjective experience become available.